Oxidation of 2-Methyl Naphthalene to 2-Naphthoic Acid with Co-Mn-Br Catalyst - Gao, Hongyan; Liu, Hongzhong; Gao, Zhixian; Eli, Wumanjiang (Asian Journal of Chemistry, 2012)
The effects of catalyst compositions, reaction parameters such as temperature, pressure and water addition on the liquid phase catalytic oxidation of 2-methyl naphthalene to 2-naphthoic acid over Co-Mn-Br catalyst have been investigated in a high-pressure reactor. It has been demonstrated that each single component of Co, Mn or Br and Co-Mn had little catalytic oxidation activity, while the oxidation was catalyzed by Co-Br, Mn-Br and Co-Mn-Br. Compared with that of Co-Br, the oxidation went smoothly with Mn-Br and higher yield was obtained but with longer reaction time. Therefore, a ternary Co-Mn-Br catalyst was investigated and a maximum product yield of 93 % with intermediate reaction time was realized. The oxidation process showed an induction time,and the time length was determined by both the catalyst composition and oxidation conditions. The induction time decreased with increasing reaction temperature and pressure. It has also been found that they required an initial temperature for the start of oxidation and a minimum pressure for complete oxidation, indicating the substantial impacts of reaction parameters. Addition of water suppressed the oxidation as denoted by both longer induction time and lower product yield, and the reaction did not happen with 7 % water addition.